2023
DOI: 10.3390/toxics11090759
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics in the Lung Tissues Associated with Blood Test Index

Shuguang Wang,
Wenfeng Lu,
Qingdong Cao
et al.

Abstract: Microplastics (MPs) have received a lot of attention and have been detected in multiple environmental matrices as a new environmental hazard, but studies on human internal exposure to MPs are limited. Here, we collected lung tissue samples from 12 nonsmoking patients to evaluate the characteristics of MPs in human lung tissues using an Agilent 8700 laser infrared imaging spectrometer and scanning electron microscopy. We detected 108 MPs covering 12 types in the lung tissue samples, with a median concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Compared to FTIR, it has the advantage of having a preliminary scan and eventually detects areas with actual particles, hence accelerating the identification process. 21 In fact, LDIR has been combined with other methods to detect MPs in human samples, such as FTIR in human sputum samples, 7 SEM in human lung, 29 cardiac and blood samples, 9 and Py-GC/MS in human testis and semen samples. 13 One downside of LDIR is that only one spectrum is recorded when two particles are adjacent to each other, while μFTIR has a better chance to discriminate between individual particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to FTIR, it has the advantage of having a preliminary scan and eventually detects areas with actual particles, hence accelerating the identification process. 21 In fact, LDIR has been combined with other methods to detect MPs in human samples, such as FTIR in human sputum samples, 7 SEM in human lung, 29 cardiac and blood samples, 9 and Py-GC/MS in human testis and semen samples. 13 One downside of LDIR is that only one spectrum is recorded when two particles are adjacent to each other, while μFTIR has a better chance to discriminate between individual particles.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown the accumulation of MPs larger than 100 μm in human sputum (median size: 75.43 μm; interquartile range: 44.67–210.64 μm) and lung tissues (11.11% of MPs larger than 100 μm). 7 , 29 However, further studies are needed to explore whether and how inhaled MPs enter the bloodstream. In vivo studies on the effects of MPs on rodents via dermal penetration are rather limited, but large MPs are unlikely to penetrate the skin barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of MPs in the respiratory system depends on their size, shape, and surface properties. Until now, only seven studies have characterized MPs in human lung tissues and bronchoalveolar lung fluid (BALF) using optimized analytical methods [2][3][4][5][6]49,50]. The results of these studies are summarized in Table 1.…”
Section: Mps Deposited In the Lungsmentioning
confidence: 99%
“…The results of these studies are summarized in Table 1. Among the polymers that were targeted in lung tissues, the predominant one were polypropylene (PP) and polyethylene terephthalate (PET) [2,4,5,49]. Focusing specifically on MP fibers, Chen et al, in 2022 [4], observed that the quantity of these fibers was twice as high in lung tumors than in normal tissues.…”
Section: Mps Deposited In the Lungsmentioning
confidence: 99%
See 1 more Smart Citation